The Theology of Nahmanides Systematically Presented - Novak, David (Brown Judaic Studies, 2020)
In Halakhah in a Theological Dimension, David Novak argues that Jewish law (halakhah) is grounded on a set of theological assumptions relating to the covenant between God and Israel. Novak's study is fundamental for understanding both his later work on the Covenant and the continuing philosophical discussion of the relationship between religious law and theology.